Descriptive and prescriptive analyses of aid allocation: approaches, issues and consequences - Mark McGillivray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Studies of the inter-recipient allocation of aid may be categorized threefold. First, there are those which attempt to explain the observed allocation of aid. Second, there are those which seek to describe or evaluate the allocation of aid against normative criteria. Third, there are those which seek to prescribe the inter-recipient allocation of aid by calculating the amounts of aid each country should receive, also based on normative criteria. This paper looks at the second and third categories of studies. It commences by looking at the different approaches or descriptive measures used, and then repeats this exercise for the prescriptive literature. It then compares the prescribed allocations of the different approaches used in the literature. These allocations are compared to actual allocations and then evaluated against various normative criteria. This reveals significant differences, both between prescribed and actual allocations and the evaluations of the different prescriptive approaches.
Keywords: F35; C43; D63; I32; 330; aid allocation; relative needs; per capita income; performance index; poverty; Entwicklungshilfe; Allokation; Theorie